Mockito made clear Java unit testing with mocks, stubs and spies - Kousen, Ken (Pragmatic Bookshelf, 2023)
Mockito is the most popular framework in the Java world for automating unit testing with dependencies. Learn the Mockito API and how and when to use stubs, mocks, and spies. On a deeper level, discover why the framework does what it does and how it can simplify unit testing in Java. Using Mockito, you'll be able to isolate the code you want to test from the behavior or state of external dependencies without coding details of the dependency. You'll gain insights into the Mockito API, save time when unit testing, and have confidence in your Java programs. If you've only ever run a few JUnit tests or injected stubs into classes to return preset values, it's time to level up your Java toolbox. Dependencies on other classes and external resources can obscure issues and make bugs hard to detect. You need to test classes in isolation to truly pinpoint your problems. And while you could write dummy classes to replace dependencies yourself, Mockito automates the process and helps you fix your code faster. Start with the Mockito API to generate fake classes for dependencies, configure how each should respond when their methods are called, and verify that the class under test interacts with dependencies the way you'd expect. Next, build unit tests with the Mockito framework and feel confident not just that methods are called, but that they are called the correct number of times and in the correct order. Along the way, follow clear test examples based on JUnit 5 to create stubs, mocks, and spies and find the source of any problems lurking in Java classes.Save time, write better code, and have more confidence in your Java programs with Mockito.
Keywords: Computer software -- Testing; Computer software -- Quality control; Java (Computer program language); Logiciels; Qualité; Contrôle; Java (Langage de programmation); Computer software; Quality control; Computer software; Testing